TREATMENT ADHERENCE AND EFFICACY OF ANTIHYPERTENSION TREATMENT IN HYPERTENSIVES IN TYUMENSKAYA ObLAST - A. Yu. Efanov; I. M. Petrov; Yu. A. Petrova; Yu. A. Vyalkina; E. M. Pochinok; I. F. Sholomov; I. V. Medvedeva; S. V. Shalaev (Российский кардиологический журнал)
Aim.  To evaluate the impact of treatment adherence on control of arterial hypertension (AH), and within a prospective study, to find out the predictors of adherence decline.Material and methods. Randomly, 321 AH patient selected, from the registry of chronic non-communicable diseases on the territory of Tymenskaya Oblast, visited physician office during year 2014. In analysis of outpatient chart, the prevalence of prescription analyzed, of the groups of antihypertension medications (AHM), including combination drugs. In 3 months (±2,1) after office visit, patients were investigated. The following characteristics were assessed: smoking status, alcohol consumption, comorbidities, economical level, employment, depression and anxiety levels, frequency of AHM intake, prevalence to treatment and BP control efficacy. In 12 months (±2,3) patients, during phone interview, answered the questions on adherence to AHM. The factors revealed, increasing the relative risk (RR) of compliance decline. RR calculated with 95% confidence interval (CI).Results. During a year, decrease of AHM intake found (from 73,2% in 3 months after office visit to 45,2% — in 12 months, р<0,01) and of its efficacy (from 51,9% in 3 months to 41,4% — in 12 months, р<0,01). Compliant to therapy patients reached target levels of BP 3,31 times (2,07-5,31), р<0,01) more often in 3 months after office visit, and 3,39 times (2,09-5,52), р<0,01) — in 12 months. As the predictors of treatment adherence were the following factors: male gender (RR =1,69 (1,06-2,70) p<0,05), age older than 65 (RR =1,72 (1,05-2,81) p<0,05), smoking (RR =1,89 (1,08-3,32) p<0,05), comorbidity 3+ (RR =2,61 (1,48-4,61) p<0,01), overconsumption of alcohol (RR =1,99 (1,02-3,89) <0,05), raised level of depression (RR =1,65 (1,09-2,69) p<0,05), no tonometer at home (RR =1,85 (1,14-2,99) p<0,05), and recommended number of AHM 3 and more (RR =2,96 (1,11-7,85) p<0,05). Higher adherence factors were female gender (RR =0,59 (0,37-0,95) p<0,05), prescription of fixed AHM combinations (RR =0,51 (0,280,923) p<0,05). Conclusion. During the study, we revealed a “patients portrait”, who are under higher chances of lower AHM adherence, and with the maximum effort is needed to retain on the prescribed treatment.